2019
DOI: 10.1111/myc.12925
|View full text |Cite
|
Sign up to set email alerts
|

A 15‐year retrospective study on the prevalence of onychomycosis in psoriatic vs non‐psoriatic patients: A new European shift from dermatophytes towards yeast

Abstract: Summary Because of their similar clinical presentation, discrimination between nail psoriasis and onychomycosis often is difficult. We aim to investigate the actual frequency of onychomycosis in psoriatic patients and to compare it between psoriatic and non‐psoriatic patients. This retrospective study included a total of 9281 patients, referring to our Mycology Laboratory from September 2003 to May 2018. The patients are divided into two groups: PsoGroup (patients with psoriasis) and non‐PsoGroup (non‐psoriati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 17 publications
(17 reference statements)
2
24
0
9
Order By: Relevance
“…It has been reported that psoriasis patients are more likely to develop onychomycosis than the general population [ 8 , 33 , 34 ]. Nevertheless, considering that both onychomycosis and nail psoriasis usually present with similar clinical features leading to difficult discrimination and ambiguous results, some reports indicate no differences in prevalence rates between psoriasis and non-psoriasis patients with clinical nail abnormalities [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that psoriasis patients are more likely to develop onychomycosis than the general population [ 8 , 33 , 34 ]. Nevertheless, considering that both onychomycosis and nail psoriasis usually present with similar clinical features leading to difficult discrimination and ambiguous results, some reports indicate no differences in prevalence rates between psoriasis and non-psoriasis patients with clinical nail abnormalities [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…45 The prevalence of onychomycosis in psoriasis patients is estimated to be between less than a quarter to one-third, [46][47][48][49][50][51][52] but was found in 50% of patients in a recent study from Italy; however, yeasts were statistically significantly more frequent in the non-psoriatic control group. 53 In a case-control study from Pakistan, nearly one-third of nail psoriasis patients had onychomycosis. 54 It was assumed that the pathogenic fungus benefits from the damaged nail of psoriasis.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…A recent evaluation of 21 million outpatient visits to dermatologists, paediatricians and general practitioners revealed that onychomycoses are the most common nail diseases in the United States 1 . In Europe, roughly half of all nails showing abnormal appearance are infected with fungi 2 …”
Section: Introductionmentioning
confidence: 99%
“…In cases with simultaneous detection of dermatophytes and ND moulds or yeasts in cultures from nail material, the dermatophytes will usually be regarded as the primary causative agent. Further fungal species are regarded as being due to secondary infection or external contamination 2 . To establish the role of ND moulds and yeasts as true pathogens, some authors suggest that the same fungus should be detected in repeated samples 5 .…”
Section: Introductionmentioning
confidence: 99%